Antioxidant capacity and interaction of endogenous phenolic compounds from tea seed oil. (15th May 2022) - Liu, Guoyan; Zhu, Wenqi; Li, Sitong; Zhou, Wanli; Zhang, Huijuan; Wang, Jing; Liu, Xiaofang; Zhang, Jixian; Liang, Li; Xu, Xin
Graphical abstract: Highlights: Fifteen endogenous phenols were characterized in tea seed oil for the first time. The antioxidant ability and the interaction type of phenols were affected by media. Combined esculetin + gentisic acid significantly prolonged lipid oxidation process. Combined quercetin + esculetin had a superior inhibitory effect on volatile compounds. Abstract: Endogenous phenols play a significant role in delaying oil rancidity. In this study, the profile of 22 endogenous phenols was determined from tea seed oil by UPLC-MS/MS, of which 15 phenols were identified for the first time. Then seven phenols with high content and strong antioxidant capacity were selected to investigate interaction using the DPPH· and Rancimat. It was found that the interaction of combinations was inconsistent in different media. Combined quercetin + esculetin, caffeoyl tartaric acid + esculetin, caffeoyl tartaric acid + gentisic acid and esculetin + gentisic acid showed synergistic antioxidant effects in oil and ethanol systems. Moreover, through the evaluation of the lipid oxidation process, combined esculetin + gentisic acid exhibited the greatest synergistic antioxidant effect. Notably, combined quercetin + esculetin had an inhibitory effect on the formation of volatile compounds. These findings may provide a basis for explaining the oxidation stability of tea seed oil.